ANALISIS EFEKTIVITAS DAN KONTRIBUSI PBB-P2 UNTUK MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN MAGETAN - Nur Anisa; Elva Nuraina; Liana Vivin Wihartanti (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
This study aims to determine how much effectiveness and contribution of PBB-P2 to increase regional income in Magetan district in 2014-2018. This type of research is descriptive qualitative. The results of this study indicate that the effectiveness of PBB-P2 in Magetan district in 2014-2018 which is included in the criteria is very effective. For its contribution in 2014-2018 it shows that the criteria are very less contributing to increasing the original income of Magetan district. While the growth of Magetan regency's regional income in 2014-2018 which was included in the criteria was unsuccessful due to the existence of several local taxes which the target was not reached.Keywords : Regional income; Effectiveness; Contribution